PENGARUH KONSUMSI AIR KELAPA MUDA TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension or high blood pressure is a medical condition characterized by increased contractions. Arteries that exceed 140/90 mmHg at rest are confirmed to have high blood pressure. Non-pharmacological treatment of hypertension can use herbal plants, such as coconut water. The purpose of this study was to determine the effect of giving coconut water on blood pressure in patients with hypertension. This study was limited from 2014 to 2023 and found 13 eligible articles sourced from the Google Scholar search engine with the keywords “coconut, blood pressure AND hypertension. The results of the study reported that from 13 articles found coconut water was effective in lowering blood pressure in patients with hypertension.